La problemática de la profesionalización de la clase política y el potencial del sorteo a través de minipúblicos deliberativos = The problem of the professionalization of the political class and the potential of the sortition through deliberative mini publics - Camarelles Queralt, Gabriel (Veritas, 2022)
One of the greatest challenges to be overcome by contemporary electoral representative democracies is to alleviate citizen disaffection and, consequently, bridge the gap between the rulers and the ruled. A certain consensus could be reached if we affirmed that the professionalization of politicians is becoming one of the obstacles that citizens face when it comes to trusting the political system. I In this sense, the main objective of this article is to reflect on the harmful effects of the professionalization of the political class and analyze the potential of the sortition as a neutralizing mechanism. In turn, find out if this, through deliberative mini publics, has or not the ability to minimize its harmful excesses and, with it, increase the degree of trust of citizens with their political representatives.